Physicochemical properties and ecotoxicological effects of yttrium oxide nanoparticles in aquatic media: Role of low molecular weight natural organic acids. (May 2016) - Zhang, Fan; Wang, Zhuang; Wang, Se; Fang, Hao; Chen, Mindong; Xu, Defu; Tang, Lili; Wang, Degao
Abstract: Understanding how engineered nanoparticles (ENPs) interact with natural organic acids is important to ecological risk assessment of ENPs, but this interaction remains poorly studied. Here, we investigate the dispersion stability, ion release, and toxicity of yttrium oxide nanoparticles (nY2 O3 ) suspensions after exposure to two low molecular weight natural organic acids (LOAs), namely benzoic acid and gallic acid. We find that in the presence of LOAs the nY2 O3 suspensions become more stable with surface zeta potential more positive or negative, accompanied by small agglomerated size. LOA interaction with nY2 O3 is shown to promote the release of dissolved yttrium from the nanoparticles, depending on the concentrations of LOAs. Toxic effects of the nY2 O3 suspensions incubated with LOAs on Scenedesmus obliquus as a function of their mixture levels show three types of signs: stimulation, inhibition, and alleviation. The mechanism of the effects of LOAs on the nY2 O3 toxicity may be mainly associated with the degree of agglomeration, particle-induced oxidative stress, and dissolved yttrium. Our results stressed the importance of LOA impacts on the fate and toxicity of ENPs in the aquatic environment. Highlights: LOAs significantly increased aqueous stability of nY2O3 in a dose-dependent manner. The presence of LOAs promoted dissolution of nY2O3 in a dose-dependent manner. Toxicity of nY2O3 with LOAs to Scenedesmus obliquus varied with mixture levels. Stimulation, inhibition, and alleviation effects of nY2O3 with LOAs were observed. Mechanism may be driven by agglomeration, oxidative stress, and dissolved yttrium. Abstract : LOAs elevate the dispersion stability of nano-Y2 O3, promote the release of dissolved yttrium, and alter the algal toxicity of nano-Y2 O3 .